Resin composition and molded article

By adding a hydrotalcite-like compound and surface-treated inorganic fillers to the polypropylene/polyphenylene ether resin composition, the water resistance and physical properties are significantly enhanced, overcoming the weaknesses of conventional compositions.

JP7656534B2Active Publication Date: 2025-04-03ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2021520770
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-17
Filing Date
2020-05-15
Publication Date
2025-04-03
Estimated Expiration
2040-05-15

AI Technical Summary

Technical Problem

Conventional polypropylene/polyphenylene ether resin compositions exhibit reduced water resistance when inorganic fillers, such as glass fibers, are added, leading to weakened physical properties when immersed in water or acid.

Method used

Incorporating a hydrotalcite-like compound into the polypropylene/polyphenylene ether resin composition, along with surface-treated inorganic fillers and polyolefins modified with unsaturated carboxylic acids, to enhance water resistance and improve the interface strength between the filler and the resin.

Benefits of technology

The modified resin composition achieves excellent water resistance and maintains physical properties even when inorganic fillers are present, effectively addressing the limitations of conventional compositions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656534000006
    Figure 0007656534000006
  • Figure 0007656534000007
    Figure 0007656534000007
  • Figure 0007656534000008
    Figure 0007656534000008
Patent Text Reader

Abstract

The present invention pertains to: a resin composition including (a) a polyphenylene ether resin, (b) a polypropylene resin, (c) an admixture, (d) an inorganic filler, and (e) a hydrotalcite-like compound; and a molded article obtained by molding said resin composition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a molded article. [Background technology]

[0002] Although polypropylene resin is excellent in moldability, water resistance, oil resistance, acid resistance, alkali resistance, etc., it has the drawback of being poor in heat resistance, rigidity, and impact resistance. Therefore, a resin composition with improved heat resistance and rigidity has been produced by blending this polypropylene resin with a polyphenylene ether resin so that the polypropylene resin forms a matrix and the polyphenylene ether resin forms dispersed particles.

[0003] As examples of such prior art, Patent Document 1 describes improving solvent resistance and impact resistance by blending polyphenylene ether with polyolefin, and Patent Documents 2 and 3 describe improving impact resistance by blending polyphenylene ether with polyolefin and a hydrogenated block copolymer.

[0004] Furthermore, Patent Documents 4 to 9 disclose that a resin composition having excellent chemical resistance and processability can be obtained by blending a specific hydrogenated block copolymer with a resin composition consisting of a polyolefin resin and a polyphenylene ether resin. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] U.S. Pat. No. 3,361,851 [Patent Document 2] U.S. Pat. No. 4,383,082 [Patent Document 3] European Patent Application Publication No. 0115712 [Patent Document 4] Japanese Patent Publication No. 63-113058 [Patent Document 5] Japanese Patent Application Publication No. 63-225642 [Patent Document 6] U.S. Pat. No. 4,863,997 [Patent Document 7] Japanese Patent Application Publication No. 3-72512 [Patent Document 8] Japanese Patent Application Publication No. 4-183748 [Patent Document 9] Japanese Patent Application Publication No. 5-320471 Summary of the Invention [Problem to be solved by the invention]

[0006] Alloy materials of polypropylene and polyphenylene ether resin are used in automotive parts and water-related parts. Water-related parts are expected to be used under water pressure and high temperatures, so they require heat resistance, water resistance, impact resistance, rigidity, and vibration fatigue properties, and therefore require inorganic filler reinforcement.

[0007] However, although the alloy material of polypropylene and polyphenylene ether resin has excellent water resistance, the interface between the inorganic filler and the resin is vulnerable to water and acid, and it has been found that the physical properties deteriorate when immersed in water or acid.

[0008] That is, conventional polypropylene / polyphenylene ether resin compositions such as those proposed in Patent Documents 1 to 9 have had a problem in terms of water resistance when glass fibers are added.

[0009] Therefore, an object of the present invention is to provide a polypropylene / polyphenylene ether resin composition that has excellent water resistance even when an inorganic filler is added. [Means for solving the problem]

[0010] Means for Solving the Problems The present inventors conducted intensive research to solve the above-mentioned problems and found that by adding a hydrotalcite-like compound to a polypropylene / polyphenylene ether composition, the decrease in physical properties in water when an inorganic filler is added is mitigated, and as a result, excellent water resistance can be obtained even when an inorganic filler is added, which was previously unattainable, and thus the present invention was completed.

[0011] That is, the present invention is as follows. [1] (a) polyphenylene ether resin, (b) polypropylene resin, (c) the block copolymer is at least one selected from the group consisting of a hydrogenated block copolymer in which at least a portion of a block copolymer comprising a polymer block a mainly composed of a vinyl aromatic compound and a polymer block b mainly composed of a conjugated diene compound is hydrogenated, a copolymer having a polystyrene block chain-polyolefin block chain, and a copolymer having a polyphenylene ether block chain-polyolefin block chain; (d) an inorganic filler; (e) a hydrotalcite-like compound; and (f) a polyolefin modified with an unsaturated carboxylic acid; The resin composition includes the inorganic filler (d) which is surface-treated with a surface treatment agent containing an acid functional group. [2] Unnotched Charpy impact strength is 10 kJ / m 2 The resin composition according to [1] above. [3] The resin composition according to [1] or [2], wherein the (d) inorganic filler contains glass fiber. [4] The resin composition according to any one of [1] to [3], wherein the (d) inorganic filler contains a fibrous filler having a fiber diameter of 11 to 20 μm. [5] The resin composition according to any one of [1] to [4], wherein the particle size of the (e) hydrotalcite-like compound is 1 nm or more and 2 μm or less. [6] The resin composition according to any one of [1] to [5], wherein the (a) polyphenylene ether resin has a reduced viscosity of 0.35 dL / g or more. [7 ] before (c) The hydrogenation rate of the admixture is 90% or more. [1]~[ 6 ] The resin composition according to any one of the preceding claims. [ 8 ] The vinyl bond content of the (c) admixture is more than 50%, [1] to [ 7 ] The resin composition according to any one of the preceding claims. [ 9 ] The phosphorus content is 0.3 mass% or less,[1]~[ 8 ] The resin composition according to any one of the preceding claims. [ 10 ] The phase containing the (a) polyphenylene ether resin forms a dispersed phase, and the phase containing the (b) polypropylene resin forms a matrix phase, [1] to [ 9 ] The resin composition according to any one of the preceding claims. [ 11 ] The average minor axis diameter of the phase containing the (a) polyphenylene ether resin is 10 nm or more and 1 μm or less, [ 10 ] A resin composition according to the present invention. [ 12 ] In 10 or more of 100 phases containing the polyphenylene ether resin (a), a linear phase containing the admixture (c) having a length of 75 nm or more is contained inside the phase containing the polyphenylene ether resin (a), [ 10 ] or [ 11 ] A resin composition according to the present invention. [ 13 ] [1]~[ 12 2. A molded article obtained by molding the resin composition according to any one of claims 1 to 11. [ 14 ] Automotive electrical and electronic parts, or water-related parts, 13 ] A molded article described in the above. Effect of the Invention

[0012] According to the present invention, a polypropylene / polyphenylene ether resin composition having excellent water resistance can be obtained even when an inorganic filler is added. [Brief description of the drawings]

[0013] [Figure 1]FIG. 1 is a TEM image showing that in the resin composition of Example 2, of 100 phases containing component (a), 10 or more of linear phases containing component (c) having a length of 75 nm or more are dispersed inside the phase containing component (a). [Diagram 2] FIG. 13 is a TEM image showing that in the resin composition of Example 24, of 100 phases containing component (a), 10 or more of linear phases containing component (c) having a length of 75 nm or more are dispersed inside the phase containing component (a). [Diagram 3] FIG. 13 is a TEM image showing that in the resin composition of Comparative Example 19, of 100 phases containing component (a), 10 or more phases containing linear (c) admixture having a length of 75 nm or more are dispersed and not contained inside the phase containing component (a). [Figure 4] FIG. 13 is a TEM image showing that in the resin composition of Comparative Example 3, of 100 phases containing component (a), 10 or more of linear phases containing the (c) admixture and having a length of 75 nm or more are dispersed and not contained inside the phase containing component (a). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present invention (hereinafter, referred to as the present embodiment) will be described in detail. Note that the present invention is not limited to the following embodiment, and can be practiced in various modifications within the scope of the gist of the present invention.

[0015] [Resin composition] The resin composition of the present embodiment is a composition containing (a) a polyphenylene ether resin, (b) polypropylene, (c) an admixture, (d) glass fiber, and (e) a hydrotalcite-like compound. By adopting the above-described configuration, the resin composition of the present embodiment can obtain a polypropylene / polyphenylene ether resin composition having excellent water resistance even when an inorganic filler is added, and furthermore, it is possible to obtain a molded article having excellent water resistance, heat resistance, impact resistance, rigidity, and vibration fatigue properties.

[0016] [(a) Polyphenylene ether resin] Specific examples of the polyphenylene ether resin (a) in this embodiment include poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), and the like, and further include polyphenylene ether copolymers such as copolymers of 2,6-dimethylphenol and other phenols (for example, copolymers with 2,3,6-trimethylphenol and copolymers with 2-methyl-6-butylphenol as described in JP-B-52-17880). Among these, particularly preferred polyphenylene ethers are poly(2,6-dimethyl-1,4-phenylene ether), copolymers of 2,6-dimethylphenol and 2,3,6-trimethylphenol, or mixtures thereof.

[0017] The method for producing component (a) is not particularly limited so long as it is a known method. Examples of the method include those described in U.S. Pat. Nos. 3,306,874, 3,306,875, 3,257,357, and 3,257,358, JP-A-50-51197, JP-B-52-17880, and JP-B-63-152628, etc.

[0018] In this embodiment, the lower limit of the preferred range of the reduced viscosity of component (a) (0.5 g / dL chloroform solution, 30° C., measured with an Ubbelohde viscometer) is 0.30 dL / g, more preferably 0.032 dL / g, and even more preferably 0.035 dL / g. The upper limit of the preferred range of the reduced viscosity is 0.80 dL / g, more preferably 0.75 dL / g, and even more preferably 0.55 dL / g. When the reduced viscosity of the (a) polyphenylene ether is within this range, it is preferable since it has excellent properties such as impact resistance and heat resistance.

[0019] In the component (a) of this embodiment, a blend of two or more polyphenylene ethers having different reduced viscosities can also be used.

[0020] In addition, various known stabilizers can be suitably used to stabilize the polyphenylene ether. Examples of the stabilizer include metal stabilizers such as zinc oxide and zinc sulfide, and organic stabilizers such as hindered phenol stabilizers, phosphorus stabilizers, and hindered amine stabilizers. The preferred blending amount of these is less than 5 parts by mass per 100 parts by mass of component (a).

[0021] Furthermore, known additives that can be added to polyphenylene ether may be added in an amount of less than 10 parts by mass per 100 parts by mass of component (a).

[0022] [(b) Polypropylene resin] (b) The polypropylene-based resin is not particularly limited, and examples thereof include homopolymers and / or copolymers having propylene as a repeating unit structure, and preferred are crystalline propylene homopolymers, crystalline propylene-ethylene block copolymers, and mixtures of crystalline propylene homopolymers and crystalline propylene-ethylene block copolymers. The crystalline propylene-ethylene block copolymer is not particularly limited, and examples thereof include those having a crystalline propylene homopolymer portion and a propylene-ethylene random copolymer portion.

[0023] The melt mass flow rate (hereinafter, also referred to as "MFR") of the (b) component is, from the viewpoint of suppressing drawdown during combustion and improving the balance between fluidity and mechanical strength, preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, and particularly preferably 0.5 g / 10 min or more, and is preferably 15 g / 10 min or less, more preferably 6 g / 10 min or less, and particularly preferably 3 g / 10 min or less. The MFR can be measured under conditions of a temperature of 230° C. and a load of 2.16 kg in accordance with ISO 1133. Specifically, the MFR can be measured by the method described in the Examples below.

[0024] The method for producing component (b) is not particularly limited, and known methods can be used. Specific examples of methods for producing polypropylene include a method of polymerizing propylene in the presence of a polymerization catalyst composition containing a titanium trichloride catalyst or a titanium halide catalyst supported on a carrier such as magnesium chloride and an alkylaluminum compound under conditions of a temperature of 0 to 100°C and a pressure of 3 to 100 atm. In the above method, a chain transfer agent such as hydrogen may be added to adjust the molecular weight of the polymer.

[0025] In addition, in the above method, in addition to the above polymerization catalyst composition, an electron donor compound can be further included in the polymerization system as an internal donor component or an external donor component in order to increase the isotacticity of the resulting polypropylene and the polymerization activity of the polymerization system. These electron donor compounds are not particularly limited, and known compounds can be used. Specific examples of the electron donor compound include ester compounds such as ε-caprolactone, methyl methacrylate, ethyl benzoate, and methyl toluate; phosphites such as triphenyl phosphite and tributyl phosphite; phosphoric acid derivatives such as hexamethylphosphoric triamide; alkoxy ester compounds; aromatic monocarboxylic acid esters; aromatic alkylalkoxysilanes; aliphatic hydrocarbon alkoxysilanes; various ether compounds; various alcohols; and various phenols.

[0026] The polymerization method in the above-mentioned method may be either a batch method or a continuous method, and the polymerization method may be solution polymerization or slurry polymerization using a solvent such as butane, pentane, hexane, heptane, or octane, or further may be bulk polymerization in a monomer or gas phase polymerization in a gaseous polymer without a solvent.

[0027] Among the methods for producing component (b), the method for producing a crystalline propylene-ethylene block copolymer is not particularly limited, and may, for example, include a method including a first step of obtaining a crystalline propylene homopolymer portion and a second step of obtaining a propylene-ethylene block copolymer portion bonded to the crystalline propylene homopolymer portion by copolymerizing the crystalline propylene homopolymer portion with ethylene and other α-olefins added as necessary. Here, the other α-olefins are not particularly limited, and may, for example, be propylene, 1-butene, 1-hexene, etc.

[0028] In this embodiment, the total content of components (a) and (b) is, when the resin composition of this embodiment is taken as 100 mass%, from the viewpoints of impact resistance and production stability of the resin composition, 30 mass% or more, preferably 35 mass% or more, and more preferably 40 mass% or more, and 80 mass% or less, preferably 75 mass% or less, and more preferably 70 mass% or less.

[0029] [(a) Polyphenylene ether resin and (b) polypropylene ratio] In this embodiment, the preferred content ratio of the (a) component to the (b) component is, when the total amount of the (a) component and the (b) component is 100 parts by mass, the content of the (a) component is 10 to 70 parts by mass and the content of the (b) component is 30 to 90 parts by mass. More preferably, the content of the (a) component is 10 to 60 parts by mass, the content of the (b) component is 40 to 90 parts by mass, and even more preferably, the content of the (a) component is 10 to 50 parts by mass, and the content of the (b) component is 50 to 90 parts by mass. When the content ratio of the (a) component to the (b) component is within this range, it is preferable because it has an excellent balance of impact resistance, heat resistance, and tensile strength. The ratio of these components in the resin composition can be determined by a calibration curve method using Fourier transform infrared spectroscopy (FT-IR).

[0030] [(c) Admixture] The resin composition of the present embodiment contains the (c) admixture, which allows the resin composition to form a matrix phase containing the (b) component and a dispersed phase containing the (a) component, thereby further improving the heat creep resistance of the resulting resin composition.

[0031] The component (c) is preferably a copolymer having a segment block chain that is highly compatible with the component (a) and a segment block chain that is highly compatible with the component (b). High compatibility means that no phase separation occurs.

[0032] Examples of segment block chains that are highly compatible with component (a) include polystyrene block chains and polyphenylene ether block chains. Examples of segment block chains that are highly compatible with the component (b) include polyolefin block chains and copolymer elastomer block chains of ethylene and α-olefin. In this specification, the component (c) is not included in the scope of the components (a) and (b).

[0033] Examples of the (c) component include one or more selected from the group consisting of hydrogenated block copolymers, copolymers having a polystyrene block chain-polyolefin block chain, and copolymers having a polyphenylene ether block chain-polyolefin block chain. Among these, hydrogenated block copolymers are preferred from the viewpoint of superior thermal stability. The (c) component may be used alone or in combination of two or more.

[0034] The hydrogenated block copolymer may be a hydrogenated block copolymer in which at least a portion of a block copolymer including a polymer block a mainly made of a vinyl aromatic compound and a polymer block b mainly made of a conjugated diene compound is hydrogenated.

[0035] A preferred specific example of the hydrogenated block copolymer is a hydrogenated block copolymer including a polymer block a mainly made of a vinyl aromatic compound and a polymer block b mainly made of a conjugated diene compound having a total amount of 1,2-vinyl bonds and 3,4-vinyl bonds of 30 to 90%. The total amount of 1,2-vinyl bonds and 3,4-vinyl bonds of the conjugated diene compound in the polymer block b is preferably 30 to 90% from the viewpoints of compatibility with the polyphenylene ether resin and vibration fatigue properties.

[0036] The polymer block a is preferably a homopolymer block of a vinyl aromatic compound, or a copolymer block of a vinyl aromatic compound and a conjugated diene compound. The phrase "mainly composed of a vinyl aromatic compound" in the polymer block a means that the polymer block a contains more than 50% by mass of vinyl aromatic compound units. From the viewpoint of achieving even better molding flowability, impact resistance, welds, and appearance, the polymer block a preferably contains 70% by mass or more of vinyl aromatic compound units.

[0037] Examples of the vinyl aromatic compound constituting the polymer block a include styrene, α-methylstyrene, vinyltoluene, p-tert-butylstyrene, diphenylethylene, etc. Among these, styrene is preferred. These may be used alone or in combination of two or more.

[0038] The number average molecular weight of the polymer block a is not particularly limited, but is preferably 15,000 or more. Also, it is preferably 50,000 or less. By setting the number average molecular weight of the polymer block a within the above range, the impact resistance of the resin composition of the present embodiment can be made more excellent. The number average molecular weight of the polymer block a can be measured by GPC (mobile phase: chloroform, standard substance: polystyrene).

[0039] The polymer block b is preferably a homopolymer block of a conjugated diene compound, or a random copolymer block of a conjugated diene compound and a vinyl aromatic compound. The phrase "mainly composed of a conjugated diene compound" in the polymer block b means that the polymer block b contains more than 50% by mass of conjugated diene compound units. From the viewpoint of achieving even better molding flowability, impact resistance, welds, and appearance, the polymer block b preferably contains 70% by mass or more of conjugated diene compound units.

[0040] Examples of the conjugated diene compound constituting the polymer block b include butadiene, isoprene, 1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, etc. Among these, butadiene, isoprene, and combinations thereof are preferred. These may be used alone or in combination of two or more.

[0041] Regarding the microstructure of polymer block b (bonding form of the conjugated diene compound), the total amount of 1,2-vinyl bonds and 3,4-vinyl bonds (hereinafter sometimes referred to as "total vinyl bond amount") relative to the total amount of vinyl bonds contained in the conjugated diene compound constituting the polymer block is preferably 30 to 90%, more preferably 45 to 90%, and even more preferably 65 to 90%. By setting the total vinyl bond amount of the conjugated diene compound in the polymer block b within the above range, the compatibility with the polypropylene resin is further improved. In particular, by setting the total vinyl bond amount to 30% or more, the dispersibility of the (a) component in the resin composition can be further improved. By setting the total vinyl bond amount to 90% or less, the excellent dispersibility of the (a) component is maintained while also being economical. In particular, when polymer block b is a polymer block mainly composed of butadiene, the total vinyl bond content of the butadiene in polymer block b is preferably 65 to 90%. The total vinyl bond amount can be measured by an infrared spectrophotometer. The calculation method can be performed in accordance with the method described in Analytical Chemistry, Volume 21, No. 8, August 1949.

[0042] The component (c) is preferably a hydrogenated block copolymer of a block copolymer containing at least a polymer block a and a polymer block b. When the polymer block a in the component (c) is represented as "a" and the polymer block b is represented as "b", examples of the component (c) include hydrogenated vinyl aromatic compound-conjugated diene compound block copolymers having structures such as ab, aba, baba, (ab-)4Si, and ababa. The Si in (ab-)4Si is a reaction residue of a polyfunctional coupling agent such as silicon tetrachloride or tin tetrachloride, or a residue of an initiator such as a polyfunctional organolithium compound.

[0043] The molecular structure of the block copolymer containing polymer block a and polymer block b is not particularly limited, and may be, for example, linear, branched, radial, or any combination thereof.

[0044] The polymer block a and the polymer block b each have a distribution of the vinyl aromatic compound or the conjugated diene compound in the molecular chain in a random manner, a tapered manner (wherein the monomer component increases or decreases along the molecular chain), a partial block manner, or any of these. Any arbitrary combination may be used.

[0045] When there are two or more of either the polymer block a or the polymer block b in the repeating unit, the two or more polymer blocks may have the same structure or different structures.

[0046] From the viewpoint of achieving even better molding flowability, impact resistance, welds, and appearance, the hydrogenated block copolymer (c) preferably contains 20 to 95% by mass of structural units derived from vinyl aromatic compounds contained in the block copolymer before hydrogenation. The lower limit of the content of the structural units may be 30% by mass or more, 40% by mass or more, 50% by mass or more, or 60% by mass or more, and the upper limit may be 85% by mass or less, 75% by mass or less, 65% by mass or less, or 55% by mass or less. The content of structural units derived from vinyl aromatic compounds can be measured by an ultraviolet spectrophotometer.

[0047] The number average molecular weight (Mn) of the block copolymer before hydrogenation is preferably 5,000 to 1,000,000. The lower limit of the number average molecular weight (Mn) may be 10,000 or more, 20,000 or more, 40,000 or more, or 60,000 or more, and the upper limit may be 800,000 or less, 500,000 or less, 200,000 or less, 100,000 or less, or 80,000 or less. The number average molecular weight (Mn) can be measured by gel permeation chromatography (GPC, mobile phase: chloroform, standard substance: polystyrene).

[0048] The molecular weight distribution of the block copolymer before hydrogenation is preferably not more than 10. The molecular weight distribution can be calculated by determining the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) measured by GPC (GPC, mobile phase: chloroform, standard substance: polystyrene).

[0049] The hydrogenation rate of the double bonds derived from the conjugated diene compound in component (c) is not particularly limited, but from the viewpoint of achieving even better heat resistance, it is preferably 50% or more, more preferably 80% or more, and even more preferably 90% or more. The hydrogenation rate can be measured by NMR.

[0050] The method for producing the hydrogenated block copolymer of component (c) is not particularly limited, and may be a known method. For example, the methods described in JP-A-47-011486, JP-A-49-066743, JP-A-50-075651, JP-A-54-126255, JP-A-56-010542, JP-A-56-062847, JP-A-56-100840, JP-A-02-300218, British Patent No. 1130770, U.S. Patent No. 3281383, U.S. Patent No. 3639517, British Patent No. 1020720, U.S. Patent No. 3333024 and U.S. Patent No. 4501857 can be mentioned.

[0051] The hydrogenated block copolymer of component (c) may be a modified hydrogenated block copolymer obtained by grafting or adding the above-mentioned hydrogenated block copolymer with an α,β-unsaturated carboxylic acid or a derivative thereof (an ester compound or an acid anhydride compound).

[0052] The modified hydrogenated block copolymer can be obtained by reacting the above-mentioned hydrogenated block copolymer with an α,β-unsaturated carboxylic acid or a derivative thereof in the presence or absence of a radical generator in a molten state, solution state or slurry state at a temperature in the range of 80 to 350°C. In this case, it is preferable that the α,β-unsaturated carboxylic acid or a derivative thereof is grafted or added to the hydrogenated block copolymer in a ratio of 0.01 to 10 mass%. Furthermore, the above-mentioned hydrogenated block copolymer and the modified hydrogenated block copolymer may be mixed in any ratio.

[0053] The content of component (c) in this embodiment, assuming the resin composition of this embodiment to be 100 mass%, from the viewpoint of the impact resistance of the resin composition, is 2 mass% or more, preferably 5 mass% or more, and more preferably 7 mass% or more, and is 30 mass% or less, preferably 25 mass% or less, and more preferably 15 mass% or less.

[0054] [(d) Inorganic filler] The surface-treated inorganic filler (d) (hereinafter also referred to simply as component (d)) used in this embodiment is not particularly limited, and any known filler can be used, with fibrous fillers and plate-like fillers being preferred.

[0055] Examples of fibrous fillers include, but are not limited to, glass fibers, carbon fibers, whiskers such as potassium titanate whiskers, calcium silicate (wollastonite), and the like. Examples of the plate-like filler include, but are not limited to, glass flakes, mica, talc, and the like. Of the above fillers, glass fiber is most preferred from the viewpoints of rigidity and water resistance. These may be used alone or in combination of two or more.

[0056] The surface treatment of the inorganic filler is not particularly limited, and examples thereof include surface treatments using various coupling agents such as silane-based and titanate-based coupling agents. In particular, it is preferable from the viewpoint of water resistance to include a surface treatment agent containing an acid functional group. From the viewpoint of increasing the adhesion between the resin and the surface-treated inorganic filler and improving the vibration fatigue properties and impact resistance of the resin composition, surface treatment using a silane coupling agent such as aminosilane or epoxysilane is preferred.

[0057] The presence or absence of an acid functional group can be determined by extracting the surface treatment agent of the glass fiber in chloroform and measuring it by Py-GC / MS, and determining whether or not a peak derived from an acid is detected. In particular, it is preferable to use glass fiber in which a peak derived from a carboxylic acid is detected, from the viewpoint of water resistance.

[0058] Examples of acids constituting a compound containing an acid functional group include unsaturated carboxylic acids or derivatives thereof, such as maleic acid, fumaric acid, itaconic acid, acrylic acid, tetrahydrophthalic acid, citraconic acid, crotonic acid, and isocrotonic acid, and examples of derivatives thereof include anhydrides, acid halides, amides, imides, esters, etc. Specific examples include maleic anhydride, acetic anhydride, succinic anhydride, monomethyl maleate, dimethyl maleate, maleimide, and glycidyl maleate.

[0059] The silane-based coupling agent (silane coupling agent) used in the surface treatment is not particularly limited, but is preferably 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethoxysilane, 3-glycidoxypropyltrimethoxysilane, or 3-glycidoxypropyltriethoxysilane.

[0060] As a method of surface treatment for inorganic filler, for example, when the inorganic filler is glass fiber, a method of applying a silane coupling agent together with a sizing agent to the surface when spinning and converging the fibrous inorganic filler, and then drying it can be mentioned. When the inorganic filler is short fiber or powder, a method of impregnating these fillers with a silane coupling agent solution, and then drying it can be mentioned. Here, the temperature during drying is preferably 100°C or higher.

[0061] When the inorganic filler is a fibrous filler, it has a fiber length of 2 mm or more when delivered from the inorganic filler manufacturer (before being kneaded in an extruder).

[0062] When the inorganic filler is fibrous, it preferably has an average fiber diameter of 20 μm or less from the viewpoint of water resistance, more preferably 5 to 15 μm from the viewpoint of the balance of mechanical properties and dimensional properties, and most preferably 12 to 14 μm. The average fiber diameter refers to the average fiber diameter per fiber of a fibrous filler measured by observing the fibrous filler with a scanning electron microscope (SEM), and may be the average of any 10 fibers.

[0063] When the inorganic filler is a plate-like filler, from the viewpoint of obtaining a sufficient reinforcing effect of the filler, the ratio (R / H) of the average plate diameter (R) to the average thickness (H) of the plates is preferably 5 or more, more preferably 10 or more, and particularly preferably 20 or more.

[0064] The content of the aforementioned (d) component, assuming the resin composition of this embodiment to be 100% by mass, is, from the viewpoints of the melt fluidity, vibration fatigue characteristics, heat resistance, surface appearance of the molded article, and specific gravity of the resin composition, 5% by mass or more, preferably 7% by mass or more, and more preferably 10% by mass or more, and is also less than 50% by mass, preferably 40% by mass or less, and more preferably 35% by mass or less.

[0065] [(e) Hydrotalcite-like compounds] As the hydrotalcite-like compound, hydrotalcites described in JP-A-60-1241 and JP-A-9-59475, for example, hydrotalcite compounds represented by the following formula, can be used. [M 2+ 1-x M 3+ x (OH) 2 ] x+ [A n- x / n mH 2 O] x- (In the formula, M 2+ is Mg 2+ , Mn 2+ , Fe 2+ , Co 2+ and other divalent metal ions, such as M 3+ Al 3+ , Fe 3+ , C 3+ A n- CO3 2- , O.H. - , H.P.O. 4 2- , S.O. 4 2- It represents an anion having n valency (especially monovalent or divalent), such as x, 0, <x<0.5であり、mは、0≦m<1である。)

[0066] The hydrotalcite-like compounds may be natural or synthetic. The hydrotalcite-like compound may be calcined hydrotalcite which has been calcined to reduce the amount of OH in the chemical structure. The hydrotalcite-like compound may be subjected to a surface treatment.

[0067] By adding the hydrotalcite-like compound, the water resistance of the resin composition is greatly improved.

[0068] Hydrotalcite-like compounds are available from Kyowa Chemical Industry Co., Ltd. under the names "DHT-4A", "DHT-4A-2", "Alcamizer", "KW-2200", etc.

[0069] It is preferable that the hydrotalcite-like compound is uniformly dispersed in the resin, and from the viewpoint of impact resistance, the average particle size of the hydrotalcite-like compound is preferably 1 nm or more and 2 μm or less, more preferably 1 nm or more and 1.5 μm or less, and even more preferably 1 nm or more and 1.0 μm or less. The average particle size refers to the average particle size per particle of the hydrotalcite-like compound measured by observing a molded piece using a scanning electron microscope (SEM), and may be the average value of the long axis and short axis measured for each particle for any 10 particles.

[0070] The content of component (e) in this embodiment, when the resin composition of this embodiment is taken as 100 mass%, from the viewpoint of the water resistance and vibration fatigue properties of the resin composition, is 0.01 mass% or more, preferably 0.03 mass% or more, and more preferably 0.05 mass% or more, and is 20 mass% or less, preferably 15 mass% or less, and more preferably 5 mass% or less.

[0071] [(f) Polyolefin modified with unsaturated carboxylic acid] For the purpose of improving the adhesion between a filler described later and the polypropylene resin forming the matrix described above, in addition to the above polypropylene resins, known modified polyolefin resins (grafted or added with 0.01 to 10% by weight of the α,β-unsaturated carboxylic acid or its derivative) obtained by reacting a polyolefin resin with an α,β-unsaturated carboxylic acid or its derivative in a molten or solution state at a temperature of 30 to 350°C in the presence or absence of a radical generator may be used, and further a mixture of the above polypropylene resins and the modified polyolefin resins in any ratio may be used.

[0072] Examples of polyolefin resins include polypropylene, polyethylene, and ethylene-propylene copolymers, and are not particularly limited as long as they are resins containing olefin as a monomer.

[0073] Examples of α,β-unsaturated carboxylic acids or derivatives thereof used as modifiers for polyolefin resins include unsaturated carboxylic acids such as maleic acid, fumaric acid, itaconic acid, acrylic acid, tetrahydrophthalic acid, citraconic acid, crotonic acid, and isocrotonic acid, and examples of derivatives thereof include anhydrides, acid halides, amides, imides, and esters. Specific examples include maleic anhydride, monomethyl maleate, dimethyl maleate, maleimide, and glycidyl maleate. Among these, anhydrides are preferred, and maleic anhydride is more preferred.

[0074] The radical generator usually includes an organic or inorganic peroxide, such as t-butyl peroxybenzoate, t-butyl hydroperoxide, methyl ethyl ketone peroxide, potassium peroxide, and hydrogen peroxide.

[0075] (f) The number average molecular weight (Mn) of the polyolefin modified with an unsaturated carboxylic acid is preferably from 20,000 to 100,000, more preferably from 25,000 to 95,000, and even more preferably from 30,000 to 95,000. The number average molecular weight (Mn) can be measured by gel permeation chromatography (GPC, mobile phase: chloroform, standard substance: polystyrene).

[0076] In this embodiment, when component (d) (inorganic filler) and component (a) (polyphenylene ether resin) are easily adhered to each other, the resin composition exhibits excellent impact resistance and vibration fatigue properties. However, the surface of the inorganic filler has low adhesive strength with resins and other substances, and even when the inorganic filler is uniformly mixed in the resin, the interfacial strength between the inorganic filler and the resin is extremely low, and the effect of improving the strength of the composition by adding the inorganic filler may not be fully obtained. In order to enhance this effect of improving strength, it is desirable to bond the resin and the inorganic filler by chemical bonds. However, since the surface of the inorganic filler has extremely low chemical reactivity, it may be difficult to cause such a chemical reaction with the inorganic filler itself. Therefore, the inorganic filler is surface-treated and (f) polyolefin modified with an unsaturated carboxylic acid is used in combination, which enables chemical bonding between the surface of the inorganic filler and the resin via component (f), and facilitates adhesion between component (d) (inorganic filler) and component (a) (polyphenylene ether resin), resulting in the resin composition exhibiting excellent impact resistance and vibration fatigue properties. Here, the inorganic filler and the surface treatment agent are likely to decompose in the presence of water, which may lead to a decrease in strength. By adding the above-mentioned hydrotalcite-like compound or by using component (d) containing a compound containing an acid functional group in the surface treatment agent, it is possible to suppress decomposition and deterioration of physical properties in the presence of water, and to obtain excellent impact resistance and vibration fatigue properties. In particular, the component (d) (inorganic filler) is preferably glass fiber from the viewpoint of strength and cost. In this case, the glass fiber is subjected to a silane coupling treatment in which a silane compound reacts with the Si-OH group present on the surface of the glass fiber, thereby enabling chemical bonding between the surface of the glass fiber and the resin via the component (f). When glass fiber is used, there is a problem that the product of the condensation reaction between the Si-OH group and the silane compound is easily decomposed in the presence of water. As described above, this problem can be solved by adding a hydrotalcite-like compound or adding a component (d) containing a compound containing an acid functional group in the surface treatment agent.

[0077] The content of component (f) in this embodiment, assuming the resin composition of this embodiment to be 100 mass%, is, from the viewpoint of the impact resistance and vibration fatigue characteristics of the resin composition, 0.1 mass% or more, preferably 0.2 mass% or more, and more preferably 0.5 mass% or more, and is 20 mass% or less, preferably 15 mass% or less, and more preferably 10 mass% or less.

[0078] [Phosphorus compounds] In this embodiment, the resin composition may contain a phosphorus-based compound. Examples of phosphorus-based compounds include organic phosphorus compounds, red phosphorus, and inorganic phosphates. The organic phosphorus compound is not particularly limited as long as it is a phosphorus compound having an organic substituent (in this embodiment, including those having a PC bond and a POC bond), and examples of the organic phosphorus compound include phosphoric acid esters (hereinafter also referred to as "phosphates"), phosphorous acid esters (hereinafter also referred to as "phosphites"), and phosphonites. More specifically, examples of the phosphates include phosphate ester compounds such as trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, tripentyl phosphate, trihexyl phosphate, tricyclohexyl phosphate, triphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, cresyl diphenyl phosphate, dicresyl phenyl phosphate, dimethyl ethyl phosphate, methyl dibutyl phosphate, ethyl dipropyl phosphate, and hydroxyphenyl diphenyl phosphate, which are used as flame retardants; modified phosphate ester compounds obtained by modifying these with various substituents; and various condensed phosphate ester compounds. Examples of phosphites include phosphorous esters such as trisnonylphenyl phosphite, triphenyl phosphite, tris(2,4-di-t-butylphenyl)phosphite, bis(2,4-di-t-butylphenyl)pentaerythritol-diphosphite, bis(2,6-di-t-butyl-4-methylphenyl)pentaerythritol-diphosphite, and 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5,5]undecane, which are also used as phosphorus-based antioxidants. Examples of phosphonites include tetrakis(2,4-di-tert-butylphenyl)4,4'-biphenylene diphosphonite and tetrakis(2,4-di-tert-butyl-5-methylphenyl)4,4'-biphenylene diphosphite.

[0079] In this embodiment, from the viewpoint of water resistance and vibration fatigue properties, the phosphorus element contained in the resin composition is preferably 0.3 mass% or less, more preferably 0.2 mass% or less, and particularly preferably 0.1 mass% or less, when the resin composition is 100 mass%. The method for measuring the phosphorus content in the resin composition includes, for example, weighing 0.25 g of a thermoplastic resin composition that has been dried in advance into a fluororesin container in a clean room, adding sulfuric acid and nitric acid thereto, and subjecting the composition to pressure acid decomposition in a microwave decomposition device to obtain a decomposition solution. 25 mL of the decomposition solution is weighed out to obtain a measurement solution, which is then measured by an ICP mass spectrometer (cobalt is the internal standard) using an absolute calibration curve method. More specifically, the phosphorus content can be measured by the method described in the examples below.

[0080] [Coloring agent] In the present embodiment, the method for coloring the resin composition is not particularly limited, and one or more colorants selected from known organic dyes and pigments and inorganic pigments can be used.

[0081] Examples of organic dyes and pigments include azo pigments such as azo lake pigments, benzimidazolone pigments, diarylide pigments, and condensed azo pigments; phthalocyanine pigments such as phthalocyanine blue and phthalocyanine green; condensed polycyclic pigments such as isoindolinone pigments, quinophthalone pigments, quinacridone pigments, perylene pigments, anthraquinone pigments, perinone pigments, and dioxazine violet; azine pigments; and carbon black. Of these, the carbon black preferably has a dibutyl phthalate (DBP) absorption of less than 250 mL / 100 g, preferably less than 150 mL / 100 g, and a nitrogen adsorption specific surface area of ​​less than 900 m2 / g, more preferably less than 400 m2 / g. When these are within these ranges, a composition that is particularly excellent in colorability, mechanical strength, and flame retardancy can be obtained. The DBP absorption and nitrogen adsorption specific surface area referred to here are values ​​measured by the methods specified in ASTM D2414 and JIS K6217, respectively. Examples of azine dyes include Solvent Black 5 (CI 50415, CAS No. 11099-03-9), Solvent Black 7 (CI 50415:1, CAS No. 8005-20-5 / 101357-15-7), and Acid Black 2 (CI 50420, CAS No. 8005-03-6 / 68510-98-5) in the Color Index.

[0082] Examples of inorganic pigments include metal oxides other than iron oxide, such as titanium oxide, zinc oxide, and chromium oxide, and composite metal oxides, such as titanium yellow, cobalt blue, and ultramarine.

[0083] The preferred amounts of the colorants added, when the entire resin composition is taken as 100% by mass, are 2% by mass or less for carbon black, 2% by mass or less for azine dyes, and 8% by mass or less for inorganic pigments, and more preferably 1% by mass or less for carbon black, 1% by mass or less for azine dyes, and 5% by mass or less for inorganic pigments. By adding the above amount, it is possible to maintain a good balance between impact resistance and mechanical properties. Furthermore, in the case of applications requiring flame retardancy, the above amount is preferable from the viewpoint of flame retardancy.

[0084] [Other additives] In this embodiment, in addition to the components described above, other inorganic fillers and additive components may be added at any stage as necessary within a range that does not impair the effects of this embodiment.

[0085] Examples of additive components include other thermoplastic resins such as polyesters and polyolefins, plasticizers (low molecular weight polyolefins, polyethylene glycol, fatty acid esters, etc.), antistatic agents, nucleating agents, flow improvers, reinforcing agents, various peroxides, spreading agents, organic heat stabilizers such as copper-based heat stabilizers and hindered phenol-based oxidative degradation inhibitors, antioxidants, ultraviolet absorbers, light stabilizers, etc.

[0086] A specific preferred amount of each of these components added is 15% by mass or less, more preferably 13% by mass or less, and even more preferably 10% by mass or less, when the entire resin composition is taken as 100% by mass.

[0087] [Morphology of resin composition] As for the morphology (dispersed form) of the resin composition of this embodiment, from the viewpoint of exhibiting chemical resistance, it is preferable that the (b) component phase is a matrix phase and the (a) component phase is a dispersed phase, and it is even more preferable that the (b) component phase is a matrix phase and the (a) component phase is a dispersed phase.

[0088] The (a) component phase contains the (a) component, and may be composed of, for example, a component containing the (a) component and the (c) component, or may be composed of a component containing the (a), the (c) component, and the (d) component, or may be composed of the (a) component.

[0089] The (b) component phase contains the (b) component, and may be composed of a component containing the (b) component and the (d) component, or may be composed of a component containing the (b) component, the (d) component, and the (e) component, or may be composed of the (b) component.

[0090] The morphology of the resin composition can be observed using a transmission electron microscope (TEM) or the like.

[0091] In particular, the (a) component phase is preferably dispersed with an average minor axis diameter of 2 μm or less, and more preferably dispersed with an average minor axis diameter of 10 nm to 1 μm from the viewpoint of impact resistance. In addition, it is preferable that the average major axis diameter / average minor axis diameter is dispersed within a range of 1-10. The average minor axis diameter and the average major axis diameter can be determined by observation using a transmission electron microscope (TEM) or the like.

[0092] The component (c) is not only contained in the component (a) phase, but also has a morphology in which the component (a) phase is surrounded by the component (c), allowing the component (a) contained in the component (a) phase to be in a more thermally stable dispersed state, which is preferable from the standpoint of impact resistance.

[0093] Furthermore, from the viewpoint of impact resistance, it is preferable that, in 10 or more of 100 phases containing the component (a), a linear phase containing the component (c) having a length of 75 nm or more is dispersed inside the phase containing the component (a). Although the reason why impact resistance is improved by being in such a dispersed state is not clear, it is presumed that the impact resistance of the resin composition is improved by forming a morphology in which the component (c) having excellent impact resistance is contained in the phase of the component (a) having relatively poor impact resistance.

[0094] The linear phase containing component (c) having a length of 75 nm or more contained inside the phase containing component (a) means a linear phase that is stained darker than component (a) in a TEM image obtained by staining components (b) and (c) with ruthenium tetroxide and observing the result, that is present in the phase containing component (a), and further that is present at a location other than the interface between the phase containing component (a) and the phase containing component (b).

[0095] In this case, with regard to those containing component (b) in the dispersed phase, there is a possibility that they are stained relatively darker than component (a) due to fusion between the dispersed phases, and therefore they are excluded from the consideration of "a phase containing component (c) in linear form having a length of 75 nm or more contained inside a phase containing component (a)."

[0096] Furthermore, in this case, all phases containing the component (c) that are not present at the interface between a phase containing the component (a) and a phase containing the component (b) are included in the above range, and even if this phase containing the component (c) is connected to a phase containing the component (c) that is present at the interface between a phase containing the component (a) and a phase containing the component (b), it is considered to be a phase containing the component (c) contained in the phase containing the component (a).

[0097] When measuring the length of the linear phase containing component (c), the phase containing component (c) that exists at the interface between the phase containing component (a) and the phase containing component (b) is excluded, and the length of the phase containing component (c) that extends away from the interface is defined as the length of the phase containing component (c) contained in the phase containing component (a).

[0098] The linear phase containing component (c) may be bent or branched, may form an arc, may be divided into two or more branches, or may be repeatedly connected. In this case, the total length of the phase containing component (c) that extends away from the interface in one phase containing component (a) is defined as the length of the phase containing component (c) contained in the phase containing component (a).

[0099] As a specific example, a state in which 10 or more of 100 phases containing component (a) contain linear phases containing component (c) having a length of 75 nm or more is shown in Figure 1. Note that Figure 1 is an image of the resin composition of Example 2 described below.

[0100] Here, Figure 1 shows an image of a linear phase containing component (c) contained inside a phase containing component (a), observed using a TEM after components (b) and (c) were stained with ruthenium tetroxide. In Figure 1, the light gray parts are the phase containing component (a), the lightest color parts are the phase containing component (b), and the dark gray or black parts are the phase containing component (c).

[0101] From the viewpoint of impact resistance, the length of the linear phase containing the component (c) is preferably 75 nm or more.

[0102] The width of the phase containing the linear (c) component contained inside the phase containing the (a) component is preferably 1 to 1000 nm, and more preferably 1 to 500 nm, from the viewpoint of obtaining even better vibration fatigue properties. The above numerical value is an average value of 100 randomly selected linear (c) components present in the (a) dispersed component phase in an image of a cross section of the resin composition observed by TEM.

[0103] Methods for controlling the morphology as described above include, for example, a method for adjusting the vinyl content of component (c), the structure and molecular weight of each block portion, a method for appropriately adjusting the molecular weight of component (a), a method for adjusting the compounding ratio of polyphenylene ether resin (a) and polypropylene resin (b), and a method for supplying polypropylene resin (b) to an extruder in portions from multiple raw material supply ports, etc. Among these, it is most effective to adjust the vinyl content and molecular weight of component (c). For example, more specifically, increasing the vinyl content of the (c) component tends to favor the morphology, but if it is too high, it may be necessary to adjust the amount added. If the ratio of the (a) component to the total of the polyphenylene ether resin (a) and the polypropylene resin (b) is too high, the (a) component becomes a matrix, and the morphology tends to be unfavorable.

[0104] Next, the conditions for obtaining a morphology image and the method for processing the obtained image will be described.

[0105] After preparing ultrathin sections using an ultramicrotome, the test pieces stained with ruthenium tetroxide for components (b) and (c) are photographed using a transmission electron microscope (product name "HT7700", manufactured by Hitachi High-Technologies Corporation) at a magnification of 10,000 times and an accelerating voltage of 100.0 kV. From the obtained observation image, a field of view is selected so that 100 or more particles of component (a) phase (dispersed phase) are included.

[0106] Next, the obtained morphology image (printed paper) was scanned using a scanner (device: RIKOH MPC5503, conditions: full-color photographic paper, resolution 300 dpi) and digitized. Image analysis software was used, and the digitized image was binarized and converted to two gradations (black / white) using the Auto condition installed in Image Pro10. As described above, (a) polyphenylene ether resin and (b) polypropylene resin are relatively white to gray, while (c) admixture is relatively black, so it can be distinguished.

[0107] From the obtained binary processed image, 100 phases (dispersed phases) containing component (a) are arbitrarily selected, and the average long axis diameter and average short axis diameter of the phase containing component (a) are measured, and the length and width of the phase containing component (c) contained inside the phase containing component (a) are measured.

[0108] In this embodiment, the result of the above measurement is an average value obtained from the three morphology images.

[0109] In addition, defects that occur on the measurement cross section (such as scratches caused when the cross section is prepared using an ultramicrotome or voids inherent in the resin) may appear in the morphology image, but the image range to be binarized should be selected so as not to include such areas.

[0110] The melt mass flow rate of the resin composition of the present embodiment is preferably from 1 to 20 g / 10 min, more preferably from 2 to 20 g / 10 min, and further preferably from 3 to 20 g / 10 min. The melt mass flow rate is a value measured in accordance with ISO1133 at 250°C under a load of 10.0 kg.

[0111] [Method of producing resin composition] The resin composition of the present embodiment can be produced by melt-kneading the above-mentioned components (a) to (e), and, if necessary, component (f) and other components.

[0112] There are no particular limitations on the method for producing the resin composition of the present embodiment, so long as it is possible to melt-knead the components (a) to (e), and, if necessary, the component (f) and other components.

[0113] A suitable method for producing the resin composition of the present embodiment includes a step (1-1) of melt-kneading the entire amount of component (a), and all or a part of component (b) and component (c) to obtain a kneaded product; a step (1-2) of adding the remainder of component (b) and component (c) (excluding the case where all of component (b) and component (c) are used in step (1-1)) to the kneaded product obtained in the step (1-1) and further melt-kneading the mixture to obtain a kneaded product; The method includes a step (1-3) of adding the entire amount of component (d) to the kneaded mixture obtained in the step (1-2) and further melt-kneading the mixture. The step of adding component (e) may be any of steps (1-1), (1-2), and (1-3), and may be added alone or in portions. The same applies to component (f).

[0114] A suitable method for producing the resin composition of the present embodiment may be a multi-stage melt-kneading method. Note that the multi-stage is not particularly limited as long as it is two or more stages. In this embodiment, the method includes, for example, In a first step, the entire amount of component (a), a portion of component (b), the entire amount of component (c), and the entire amount of component (e) are melt-kneaded to obtain pellets; In a second step, the pellets obtained in the first step, the remainder of component (b), and component (d) are added, and if necessary, component (f) is added, followed by further melt-kneading; Includes. In this case, the entire amount of component (b) may be added in the second stage.

[0115] Furthermore, a preferred method for producing the resin composition of the present embodiment is to produce a resin composition containing a specific component at a high concentration. Also included is a masterbatch method in which a resin composition (masterbatch) containing each component is prepared in advance, and then the masterbatch is diluted to obtain a resin composition containing each component at a desired concentration.

[0116] In this embodiment, the method includes, for example, In a first step, the entire amount of component (a), a portion of component (b), the entire amount of component (c), and the entire amount of component (d) are melt-kneaded to obtain master batch pellets containing component (d) at a concentration higher than that of the final composition; In a second stage, the master batch pellets and the remainder of component (b) and, if necessary, component (f) are added, and the mixture is further melt-kneaded to obtain a final composition; Includes. In this case, the entire amount of component (b) may be added in the second stage.

[0117] The melt kneader suitably used for melt kneading each component in the above-mentioned production method is not particularly limited, and examples thereof include extruders such as multi-screw extruders such as single-screw extruders and twin-screw extruders, rolls, kneaders, Brabender plastographs, Banbury mixers, etc., and from the viewpoint of kneading properties, twin-screw extruders are particularly preferred. Specific examples of twin-screw extruders include the ZSK series manufactured by Coperion, the TEM series manufactured by Toshiba Machine Co., Ltd., and the TEX series manufactured by The Japan Steel Works, Ltd.

[0118] A preferred embodiment in which an extruder such as a single screw extruder or a multi-screw extruder such as a twin screw extruder is used will be described below.

[0119] The type, specifications, etc. of the extruder are not particularly limited and may be any known type.

[0120] The L / D (effective barrel length / inner barrel diameter) of the extruder is preferably 20 or more, more preferably 30 or more, and is preferably 75 or less, more preferably 60 or less.

[0121] The extruder may be configured to include two or more different raw material supply ports, two or more vacuum vents, and one or more liquid addition pumps (described later). In terms of impact resistance, it is more preferable to arrange these facilities in such a way that a first raw material supply port is provided upstream in the direction in which the raw materials flow, a first vacuum vent is provided downstream of the first raw material supply port, a second raw material supply port is provided downstream of the first vacuum vent, a liquid addition pump is provided downstream of the second raw material supply port, and a second vacuum vent is provided downstream of the liquid addition pump.

[0122] The method of supplying the raw material through the second raw material supply port is not particularly limited, and may be a method of simply adding the raw material through the upper opening of the raw material supply port, or a method of adding the raw material through the side opening using a forced side feeder. In particular, from the viewpoint of stable supply, the method of adding the raw material through the side opening using a forced side feeder is preferred.

[0123] When the components are melt-kneaded, the melt-kneading temperature may usually be 270 to 320°C.

[0124] In particular, from the viewpoint of exhibiting the smoke generation property and chemical resistance of the resin composition, it is preferable that the temperature be 300° C. or more and 320° C. or less between the first raw material supply port and the second raw material supply port.

[0125] Here, from the viewpoint of expressing the smoke generation properties and chemical resistance of the resin composition, it is preferable to set different temperatures between the first raw material supply port and the second raw material supply port and the portion downstream of the second raw material supply port. Specifically, it is preferable to set the temperature between the first raw material supply port and the second raw material supply port to 300°C or higher and 320°C or lower, and to set the temperature downstream of the second raw material supply port to 270°C or higher and lower than 300°C.

[0126] The screw rotation speed is not particularly limited and may usually be 100 to 1200 rpm.

[0127] [Molded body] The molded article of the present embodiment is made of the resin composition of the present embodiment described above. Molded articles of the resin composition of the present embodiment include, but are not limited to, automobile parts, interior and exterior parts of electrical equipment, and other parts. Examples of automobile parts include, but are not limited to, exterior parts such as bumpers, fenders, door panels, various moldings, emblems, engine hoods, wheel caps, roofs, spoilers, and various aero parts; interior parts such as instrument panels, console boxes, and trims; secondary battery container parts mounted on automobiles, electric vehicles, hybrid electric vehicles, and the like; and lithium ion secondary battery parts. In addition, examples of interior and exterior parts of electrical equipment include, but are not limited to, cabinets and chassis of various computers and their peripherals, other office automation equipment, televisions, videos, and various disc players, as well as parts used in refrigerators, air conditioners, and liquid crystal projectors. Other parts include electric wires and cables obtained by applying a coating to metal conductors or optical fibers, fuel cases for solid methanol batteries, fuel cell water pipes, water cooling tanks, boiler exterior cases, ink peripheral parts and members of inkjet printers, furniture (chairs, etc.), chassis, water piping, and joints.

[0128] [Method of manufacturing molded body] The molded article of this embodiment can be produced by molding the above-mentioned resin composition of this embodiment. The method for producing the molded body of this embodiment is not particularly limited, and examples thereof include injection molding, extrusion molding, extrusion profile molding, blow molding, and compression molding. From the viewpoint of more effectively obtaining the effects of this embodiment, injection molding is preferred. EXAMPLES

[0129] The present embodiment will be described below with reference to examples, but the present embodiment is not limited to these examples.

[0130] Working Example , reference example The raw materials used for the resin compositions and molded articles of the comparative examples are shown below.

[0131] (a) Polyphenylene ether resin (a-1) Polyphenylene ether resin obtained by oxidative polymerization of 2,6-xylenol The polyphenylene ether resin had a reduced viscosity (0.5 g / dL, chloroform solution, measured at 30° C.) of 0.52 dL / g. (a-2) Polyphenylene ether resin obtained by oxidative polymerization of 2,6-xylenol The polyphenylene ether resin had a reduced viscosity (0.5 g / dL, chloroform solution, measured at 30° C.) of 0.40 dL / g. (a-3) Polyphenylene ether resin obtained by oxidative polymerization of 2,6-xylenol The polyphenylene ether resin had a reduced viscosity (0.5 g / dL, chloroform solution, measured at 30° C.) of 0.32 dL / g.

[0132] (b) Polypropylene (b-1) Polypropylene homopolymer with MFR of 15 g / 10 min (b-2) Polypropylene homopolymer with MFR of 2 g / 10 min (b-3) Polypropylene homopolymer with MFR of 0.4 g / 10 min The MFR was measured in accordance with ISO1133 at a temperature of 230°C and a load of 2.16 kg.

[0133] (c) Admixtures (c-1) A block copolymer having a block structure of II-I-II-I was synthesized by a known method, with polymer block I being made of polystyrene and polymer block II being made of polybutadiene. The synthesized block copolymer was hydrogenated by a known method. The polymer was not modified. The physical properties of the obtained unmodified hydrogenated block copolymer are shown below. Polystyrene content in block copolymer after hydrogenation: 44% by mass, number average molecular weight (Mn) of block copolymer after hydrogenation: 95,300, weight average molecular weight (Mw): 113,600, 1,2-vinyl bond amount (total vinyl bond amount) in polybutadiene block after hydrogenation: 79%, hydrogenation rate of polybutadiene portion constituting polybutadiene block: 99% (c-2) A block copolymer having a block structure of II-I-II-I was synthesized by a known method, with polymer block I being made of polystyrene and polymer block II being made of polybutadiene. The synthesized block copolymer was hydrogenated by a known method. The polymer was not modified. The physical properties of the obtained unmodified hydrogenated block copolymer are shown below. Polystyrene content in block copolymer after hydrogenation: 66% by mass, number average molecular weight (Mn) of block copolymer after hydrogenation: 57,000, weight average molecular weight (Mw): 60,400, 1,2-vinyl bond amount (total vinyl bond amount) in polybutadiene block after hydrogenation: 41%, hydrogenation rate of polybutadiene portion constituting polybutadiene block: 99%

[0134] (d) Inorganic filler (d-1) Glass fiber with an average fiber diameter of 13 μm was surface-treated with a surface treatment agent containing an acid functional group. It was confirmed by measurement using Py-GC / MS that the surface treatment agent contained an acid functional group. (d-2) Glass fiber with an average fiber diameter of 13 μm. (d-3) Glass fiber with an average fiber diameter of 10.5 μm.

[0135] (e) Hydrotalcite-like compounds (e-1) Kyowa Chemical Industry Co., Ltd. DHT-4C hydrotalcite, Mg 4.5 Al 2 (OH) 13 CO 3 3.5H 2 O (representative structure), surface treatment with higher fatty acid, average particle size 0.40 μm. (e-2) Kyowa Chemical Industry KW2200 Calcined hydrotalcite, Mg 0.7 Al 0.3 O 1.15 (Representative structure), average particle size 0.45μm.

[0136] (f) Polyolefin modified with unsaturated carboxylic acid (f-1) Polypropylene modified with maleic anhydride, number average molecular weight (Mn): 60,000, weight average molecular weight (Mw): 91,000 (f-2) Polyethylene propylene modified with maleic anhydride, number average molecular weight (Mn): 32,000, weight average molecular weight (Mw): 83,000

[0137] (Other ingredients) Organophosphorus compounds Bisphenol A condensed phosphate ester: Daihachi Chemical Co., Ltd., product name "CR-741", the main component in the following chemical formula is n=1 (approximately 85% by area ratio according to liquid chromatography analysis, acid value = 0.01 KOHmg / g) [ka]

[0138] Each Example , reference example As the melt kneader used in producing the resin compositions of the comparative examples, a twin-screw extruder (ZSK-25, manufactured by Coperion) was used. The L / D of the extruder was set to 35. The first raw material supply port was provided upstream of the flow direction of the raw material, the second raw material supply port was provided downstream of this, and a vacuum vent was provided further downstream. The raw material was supplied to the second supply port by using a side feeder from the extruder side opening. Using the extruder set up as above, (a) polyphenylene ether resin, (b) polypropylene, (c) admixture, (d) surface-treated inorganic filler, (e) hydrotalcite-like compound, and (f) polyolefin modified with unsaturated carboxylic acid were blended in the composition shown in Table 1, and melt-kneaded under the conditions of extrusion temperature 270 to 320 ° C, screw rotation speed 300 rpm, and discharge rate 20 kg / hour to obtain pellets.

[0139] The resin pellets obtained above were fed into a small injection molding machine (product name: IS-100GN, manufactured by Toshiba Machine Co., Ltd.) set at 240-280°C, and test pieces for evaluation in each test described below were prepared under the condition of a mold temperature of 60°C. JIS K7139 Type A1 test pieces were prepared and left to stand in an 80°C environment for 24 hours using a gear oven for heat history treatment. These test pieces were used as test pieces for measuring impact resistance and water resistance and for observing morphology. In addition, a Type III test piece was created in accordance with the cantilever bending test method of JIS-7119 for evaluating vibration fatigue properties.

[0140] (1) Morphology From the obtained test pieces for morphology observation, ultrathin sections with a thickness of 80 nm were prepared using an ultramicrotome and stained with ruthenium tetroxide. The obtained samples were observed at a magnification of 10,000 times using a TEM (HT7700, manufactured by Hitachi Gai Technologies). From the observed images, the length of the phase containing component (c) contained in the phase containing component (a) was measured by the method described above. If 10 or more of 100 phases containing component (a) had linear phases containing component (c) of 75 nm or more contained inside the phase containing component (a), they were marked with an "O" and if not, they were marked with an "X". Similarly, the average minor axis diameter of the phase containing component (a) was determined from the observed images by the method described above. Those having an average minor axis diameter of 10 nm or more and 1 μm or less were marked with "○", and those not having an average minor axis diameter were marked with "×".

[0141] (2) Phosphorus content The surface of the pellets of the obtained resin composition was washed with pure water in a clean room. Then, 0.25 g was weighed out to prepare a sample. This sample was placed in a decomposition vessel made of Teflon (registered trademark), sulfuric acid and nitric acid were added thereto, and the sample was subjected to pressure acid decomposition using a microwave decomposition device. Then, 25 mL of the decomposition liquid was measured and used as a measurement solution. This measurement solution was measured by an absolute calibration curve method using an ICP mass spectrometer (internal standard: cobalt), and a component analysis was performed to calculate the phosphorus element content (mass%).

[0142] (3) Impact resistance The test pieces for measuring impact resistance and water resistance prepared by the above molding were cut to prepare test pieces for measuring Charpy impact strength. No notches were made at this time. The Charpy impact strength (kJ / m 2 ) was measured. The evaluation criteria were such that the higher the measured value, the better the impact resistance.

[0143] (4) Melt Mass Flow Rate The resulting pellets of the resin composition were evaluated for melt mass flow rate (g / 10 min) at 250° C. under a load of 10.0 kg in accordance with ISO1133. The evaluation criteria were such that the larger the measured value, the better the fluidity.

[0144] (5) Water resistance The above-mentioned test piece for measuring Charpy impact strength was used, and after being kept at a constant temperature and humidity of 23 degrees and 50% humidity for 24 hours, the Charpy impact strength (kJ / m 2 ) was measured in A (kJ / m 2 ) was decided. The test piece was placed in a pressure cooker (TPC-221 manufactured by ESPEC) at 130°C and 100% humidity for 350 hours, then removed and held at constant temperature and humidity of 23°C and 50% humidity for 24 hours. After that, the Charpy impact strength (kJ / m 2 ) was measured as B(kJ / m 2 ) was decided. Here, as an index of water resistance, the property retention rate C (%) after being placed in a pressure cooker was calculated using the following formula. C = (A / B) × 100 The evaluation criteria were such that the higher the measured value, the more excellent the water resistance.

[0145] (6) Vibration fatigue characteristics The JIS-7119 type III test piece for the cantilever bending test prepared by the above molding was subjected to a bending fatigue test in accordance with JIS-7119 under the conditions of temperature: 90°C, frequency: 30Hz, and load: 20MPa, and the number of vibrations (times) at which the test piece broke was determined using a bending fatigue tester (product name: B70-TH, manufactured by Toyo Seiki Seisakusho Co., Ltd.). Measurements were performed with n=4, and the average value was shown. If the test piece did not break after 1,000,000 or more times, the test was discontinued, and it was noted in the table of examples that the test piece did not break. As an evaluation criterion, the greater the number of vibrations until breakage, the more excellent the vibration fatigue resistance characteristics were judged to be.

[0146] (Examples 1 to 5, 8 to 21、24、 25, Reference examples 6, 7, 22、23、 Comparative Examples 1 to 23) For each of the Examples, Reference Examples, and Comparative Examples, physical property tests were carried out using the above-mentioned measurement methods (1) to (5). The results are shown in Tables 1 and 2.

[0147] [Table 1-1] [Table 1-2]

[0148] [Table 2-1] [Table 2-2] [Industrial Applicability]

[0149] According to the present invention, a polypropylene / polyphenylene ether resin composition having excellent water resistance can be obtained even when an inorganic filler is added.

Claims

1. (a) a polyphenylene ether resin, (b) a polypropylene resin, (c) a hydrogenated block copolymer in which at least a portion of a block copolymer containing a polymer block a mainly made of a vinyl aromatic compound and a polymer block b mainly made of a conjugated diene compound is hydrogenated, a copolymer having a polystyrene block chain-polyolefin block chain, and a copolymer having a polyphenylene ether block chain-polyolefin block chain, (d) an inorganic filler, (e) a hydrotalcite-like compound, and (f) a polyolefin modified with an unsaturated carboxylic acid, The resin composition includes the inorganic filler (d) which is surface-treated with a surface treatment agent containing an acid functional group.

2. Unnotched Charpy impact strength is 10 kJ / m 2 The resin composition according to claim 1 .

3. The resin composition according to claim 1 or 2, wherein the inorganic filler (d) comprises glass fibers.

4. The resin composition according to any one of claims 1 to 3, wherein the (d) inorganic filler comprises a fibrous filler having a fiber diameter of 11 to 20 µm.

5. The resin composition according to any one of claims 1 to 4, wherein the particle size of the (e) hydrotalcite-like compound is 1 nm or more and 2 µm or less.

6. The resin composition according to any one of claims 1 to 5, wherein the polyphenylene ether resin (a) has a reduced viscosity of 0.35 dL / g or more.

7. The resin composition according to any one of claims 1 to 6, wherein the hydrogenation rate of the (c) admixture is 90% or more.

8. The resin composition according to any one of claims 1 to 7, wherein the vinyl bond content contained in the (c) admixture is more than 50%.

9. The resin composition according to any one of claims 1 to 8, wherein the phosphorus content is 0.3 mass% or less.

10. The resin composition according to any one of claims 1 to 9, wherein the phase containing the (a) polyphenylene ether resin forms a dispersed phase, and the phase containing the (b) polypropylene resin forms a matrix phase.

11. The resin composition according to claim 10, wherein the average minor axis diameter of the phase containing the polyphenylene ether resin (a) is 10 nm or more and 1 μm or less.

12. 12. The resin composition according to claim 10, wherein in 10 or more of 100 phases containing the polyphenylene ether resin (a), a linear phase containing the admixture (c) having a length of 75 nm or more is contained inside the phase containing the polyphenylene ether resin (a).

13. A molded article obtained by molding the resin composition according to any one of claims 1 to 12.

14. The molded article according to claim 13, which is an automotive electric / electronic part or a water-related part.

Citation Information

Patent Citations

  • Polyphenylene ether resin compositions containing an olefin polymer or copolymer

    EP0115712A1

  • Resin composition

    JP1988113058A

  • Polymer composition

    JP1988225642A

  • Hydrogenated diene copolymer, modified hydrogenated diene copolymer and composition containing the same

    JP1991072512A

  • Polyphenylene ether resin composition

    JP1992183748A